PERAN KETERLIBATAN ORANG TUA MELALUI PoSKesGi DALAM KOMUNITAS KELUARGA TERHADAP PERUBAHAN NILAI OHIS ANAK KEBUTUHAN KHUSUS - Endah Aryati Ekoningtyas; Diyah Fatmasari; Ani Subekti; Wahyu Jati Dyah Utami; Irmanita Wiradona (Jurnal Kesehatan Gigi, 2021)
Maintenance of dental and oral hygiene is very important for dental and oral health. The OHIS value can be used as an indicator of dental and oral hygiene. Children with special needs are children who have limitations in one or several abilities. The need for the role of a mother is not a short period so there must be a sense of togetherness in the community to foster togetherness and care for children with special needs, PoskesGi is a forum for Peer Group activities which is a form of community empowerment where the participants are family communities who have children with special needs. The purpose of this study was the influence of the form of peer groups as a means of fostering parental involvement in the maintenance of dental and oral hygiene of children with special needs.The research is descriptive analytic by using a cross sectional study design approach and the sampling technique is the total sampling method. The data analysis method used was statistical calculations using the Wilcoxon test.The results showed that there was a significant difference (p, 0.05) between OHIS before and after the involvement of parents in the Peer Group in the family community of Children with Special Needs. The conclusion is that there is an influence of parental involvement in Peer Group activities for the Children with Special Needs community in changing the OHIS value of children with special needs.Keywords: Community Empowerment, PosKesGi, Peer Group, OHIS for children with special needs